2022
DOI: 10.1093/jom/ufac001
|View full text |Cite
|
Sign up to set email alerts
|

Research on performance optimization of gas–liquid ejector in multiphase mixed transportation device

Abstract: In the process of oil and gas extraction, a system that uses a pump and reversing mechanism to achieve high-efficiency export of gas–liquid mixture is devised. A gas–liquid ejector is fitted in the front of the device to boost pressure inside the tank in order to store more gas in the tank under a given volume. To meet the working conditions of gas–liquid high-efficiency transport device and obtain a larger outlet pressure and better ejection performance, this paper investigates the effect of outlet pressure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…As discussed in section , possible liquid accumulation on the bottom plate of the cylinder-shaped chamber (see Figures f and h) results in a decrease in the gas–liquid contact time due to the nonuniformity of the gas–liquid layer. A good gas–liquid dispersion (see Figure g) can be obtained by an increase of the gas flow rate as the increased momentum transfer results in higher liquid velocities in the vortex chamber. ,, Some literature on gas–liquid reactor geometry optimization claims that the reactor size affects the gas–liquid velocity inside the reactor. The cylinder-shaped chamber with a lower chamber height but with the same chamber diameter (as shown in Case 3 in Figure ) is designed to study the effect of chamber volume (chamber height). It should be noted that the chamber volume of Case 3 is still larger than that of the base case.…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in section , possible liquid accumulation on the bottom plate of the cylinder-shaped chamber (see Figures f and h) results in a decrease in the gas–liquid contact time due to the nonuniformity of the gas–liquid layer. A good gas–liquid dispersion (see Figure g) can be obtained by an increase of the gas flow rate as the increased momentum transfer results in higher liquid velocities in the vortex chamber. ,, Some literature on gas–liquid reactor geometry optimization claims that the reactor size affects the gas–liquid velocity inside the reactor. The cylinder-shaped chamber with a lower chamber height but with the same chamber diameter (as shown in Case 3 in Figure ) is designed to study the effect of chamber volume (chamber height). It should be noted that the chamber volume of Case 3 is still larger than that of the base case.…”
Section: Resultsmentioning
confidence: 99%
“…The dimensionless parameter head ratio h indicates the ratio of the energy obtained by the mixed fluid to the energy consumed by the power gas Equation ( 6). The parameter η Equation (7) indicates that the product of mass flow ratio q and head ratio h represents the efficiency of the jet pump,…”
Section: The Annular Jet Pump Efficiencymentioning
confidence: 99%
“…Current research on gas‐driven jet pumps focuses on structural features and the effect of different media on their performance. Zhao et al 7 found that the area ratio and nozzle diameter of the gas–liquid jet pump have a significant effect on the mixing performance of the pump, nozzles of different diameters will correspond to different optimal area ratios, and a reasonable combination of structures will raise the efficiency of the pump. Chen et al 8 indicated that the outlet position of the nozzle and the length of the throat are the key factors affecting the performance of the pump.…”
Section: Introductionmentioning
confidence: 99%
“…CFD models are an alternative method for studying jet pumps. This method allows the exploration of effects of geometrical [11], [12] and operational parameters [13], [14] on jet pump performance and the internal flow field [15]. Xu et al [16] used Large Eddy Simulation (LES) to investigate the turbulent flow field of an annular jet pump.…”
Section: Introductionmentioning
confidence: 99%